Recurrence of diverticulitis after prophylactic sigmoidectomy: an underestimated problem?. (4th December 2022) - Mathilde, Aubert; Mege, Diane; Monsinjon, Marie; Giacca, Massimo; Panis, Yves
Abstract: Aim: Several papers have been published about the risk of recurrence after an attack of diverticulitis treated conservatively. However, very few papers have been devoted to the risk of postoperative recurrence of diverticulitis (PRD) after prophylactic sigmoidectomy (PS). The aim of this work was to report the rate of PRD after PS and to assess possible risk factors for recurrence after surgery. Method: All consecutive patients who underwent elective laparoscopic PS for diverticulitis between 2005 and 2019 were retrospectively included. PRD was assessed. Results: Three hundred and sixty four patients (199 men, mean age 54 ± 13 years) were included. Among these, 26 (7%) presented with 1.7 ± 1 (range 1–4) episodes of recurrence of diverticulitis after a mean delay of 44 ± 39 months (1 month–11 years) after surgery. Patients who presented with postoperative recurrence of diverticulitis were younger (46 ± 11 vs. 55 ± 13 years, p = 0.002) and more frequently had uncomplicated diverticulitis [15/26 (58%) vs. 97/338 (29%), p = 0.002] and more than two previous episodes before PS [17/26 (65%) vs. 132/338 (39%), p = 0.009] than patients without PRD. After multivariate analysis, two independent risk factors for PRD were identified: patients with more than two episodes before PS (OR = 3.3, 95% CI = 1.2–9, p = 0.005) and age < 50 years (OR = 4.5, 95% CI = 2–11, p = 0.001). If both factors were present, recurrence reached 18% (9/51). Conclusion: Postoperative recurrence of diverticulitis is rare (7%) after PS for diverticulitis. Some patients (i.e. those with more than two episodes before PS and/or age <50 years) could be exposed to a higher risk of recurrence (up to 18%), making prophylactic surgery questionable in these patients.